2023
DOI: 10.1002/phar.2860
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug–drug interactions among U.S. adults treated with nirmatrelvir/ritonavir: A cross‐sectional study of the National Covid Cohort Collaborative (N3C)

Abstract: ImportanceNirmatrelvir/ritonavir has potential to interact with many drugs.ObjectiveTo estimate the prevalence of potential moderate to severe drug‐drug interactions (DDIs) involving nirmatrelvir/ritonavir, identify interacting medications, and evaluate risk factors associated with potential DDIs.Design, Setting, and ParticipantsCross‐sectional study using electronic health records from the National COVID Cohort Collaborative Enclave, one of the largest COVID‐19 data resources in the United States. Study parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In summary, nirmatrelvir may not be relevant for clozapine metabolism. I completed a PubMed search "nirmatrelvir [Title] and drug interactions," which produced a study 16 in Pharmacotherapy, a pharmacy journal that I trust. This article confirmed that DDIs due to nirmatrelvir/ritonavir as the perpetrator drug are really explained by ritonavir's effects; several times, I have been consulted on the risk-benefits of the combination of ritonavir with antipsychotics.…”
Section: Tdp and Pneumonia Risks In Clozapine Patientsmentioning
confidence: 99%
“…In summary, nirmatrelvir may not be relevant for clozapine metabolism. I completed a PubMed search "nirmatrelvir [Title] and drug interactions," which produced a study 16 in Pharmacotherapy, a pharmacy journal that I trust. This article confirmed that DDIs due to nirmatrelvir/ritonavir as the perpetrator drug are really explained by ritonavir's effects; several times, I have been consulted on the risk-benefits of the combination of ritonavir with antipsychotics.…”
Section: Tdp and Pneumonia Risks In Clozapine Patientsmentioning
confidence: 99%
“…Its component ritonavir is used as a boosting agent to reach and maintain therapeutic drug concentrations of nirmatrelvir throughout the dosing interval by inhibiting a variety of cytochrome P450 (CYP) isozymes including CYP3A4, which is the main CYP involved in nirmatrelvir metabolism. Older patients or patients with chronic conditions such as cardiovascular disease or diabetes have a higher risk of suffering a severe course of SARS-CoV-2 and often concurrently take additional medications [1]. Intake of nirmatrelvir/ritonavir within 3 days after being positive for SARS-CoV-2 significantly reduces the risk in this population [2].…”
Section: Introductionmentioning
confidence: 99%